Telescopes - Barter, James 1946-; Gale Group (Detroit, Mich. Lucent Books, 2005)
Discusses the invention of the telescope, its uses in the advancement of science, and its benefit to society.
Tools to answer cosmic questions -- The first to see -- The era of the giants -- Radio telescopes : discovering the invisible universe -- Observing the violent universe : X-rays and gamma rays -- Hubble -- Peering into the future.
Electronic reproduction.
Keywords: Telescopes -- Juvenile literature; Electronic books